Pemeriksaan Kesehatan dan Bakti Sosial sebagai Strategi Peningkatan Kesadaran Deteksi Dini Penyakit pada Masyarakat - Wenny Nugrahati Carsita; Mira Wahyu Kusumawati; Winani (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
Public awareness of routine health screenings remains low, resulting in many cases of non-communicable diseases such as hypertension and diabetes mellitus going undetected in their early stages and posing a risk of complications. One solution is to organize health screenings combined with community service activities. The aim of these activities is to provide health information while raising awareness of the importance of early detection. The stages of the activity included participant registration, blood pressure measurement, random blood sugar testing, and health consultations. A total of 30 people participated enthusiastically. The results identified that 21 participants (70%) had high blood pressure, and 7 participants (23.3%) had elevated blood sugar levels. The results of the activity indicate that the prevalence of non-communicable diseases remains quite high, necessitating ongoing prevention, monitoring, and education efforts within the community.